QUALITY OF SERVICE AND CUSTOMER SATISFACTION OF THE PERUVIAN LOGISTICS OF THE EAST PORT TERMINAL, PUCALLPA, PERU - Bollet Ramírez, Frank (2020)
The aim was to determine the relationshipbetween quality of service and satisfaction of usersof the company Logística Peruana del Oriente S.A.from the city of Pucallpa - Peru in 2019. The researchwas basic, with a simple correlational design, theinstruments were two survey questionnaires. Toevaluate the quality of the service, the Service Quality(SERVQUAL) model was used, which measuresthis variable based on the difference in customerexpectations and perceptions. A census was applied,taking the 50 crew members of the vessels that makeuse of the company's service. It is concluded thatthere is a positive and significant relationship betweenthe variables, with a Rho Spearman correlationcoefficient of 0.571 and significance of 0.000 ? 0.05.